The Rights and Obligations of Students Through Civics Learning at the Ibnu Sina Genteng Vocational School-Banyuwangi - Eny Puspita Ningrum️ (Social Studies Conference Proceedings, 2021)
Rights and obligations are one of the critical mutually sustainable components that need to be maintained by the State. Rights and obligations have fundamental values , so rights and obligations must run in balance in practice. So the purpose of this paper aims to determine the installation of the concept of rights and obligations through Civics learning in students. The writing of this article uses a qualitative approach. The results obtained from this study indicate that students can know and understand their rights and obligations as students and as good citizens through Civics learning. Civics learning is a subject that focuses on the formation of citizens who can carry out their rights and obligations as Indonesian citizens who are intelligent and reasonable, dedicated, skilled, and have character. Understanding the concept of rights and obligations through Civics learning must be instilled in students from an early age so that when students are adults, they can become provisions in their practice.